Manual for intelligent energy services - Hansen, Shirley J., 1928- (Fairmont Press ; M. Dekker, 2002)
A specialist in performance contracting, Hansen offers owners and managers advice on how to asses their company's energy conditions and then determine outsourcing strategies for needed services. She devotes one section to securing assistance from energy service companies on financing and expertise.